The association between obesity and dengue severity among pediatric patients: A systematic review and meta-analysis - Zulkipli, Mohd Syis; Dahlui, Maznah; Jamil, Nor'ashikin; Peramalah, Devi; Hoe, Victor Chee Wai; Bulgiba, Awang; Rampal, Sanjay (Public Library of Science, 2018)
Background: Severe dengue infection often has unpredictable clinical progressions and outcomes. Obesity may play a role in the deterioration of dengue infection due to stronger body immune responses. Several studies found that obese dengue patients have a more severe presentation with a poorer prognosis. However, the association was inconclusive due to the variation in the results of earlier studies. Therefore, we conducted a systematic review and meta-analysis to explore the relationship between obesity and dengue severity. Methods: We performed a systematic search of relevant studies on Ovid (MEDLINE), EMBASE, the Cochrane Library, Web of Science, Scopus and grey literature databases. At least two authors independently conducted the literature search, selecting eligible studies, and extracting data. Meta-analysis using random-effects model was conducted to compute the pooled odds ratio with 95% confidence intervals (CI). Findings: We obtained a total of 13,333 articles from the searches. For the final analysis, we included a total of fifteen studies among pediatric patients. Three cohort studies, two case-control studies, and one cross-sectional study found an association between obesity and dengue severity. In contrast, six cohort studies and three case-control studies found no significant relationship between obesity and dengue severity. Our meta-analysis revealed that there was 38 percent higher odds (Odds Ratio = 1.38; 95% CI:1.10, 1.73) of developing severe dengue infection among obese children compared to non-obese children. We found no heterogeneity found between studies. The differences in obesity classification, study quality, and study design do not modify the association between obesity and dengue severity. Conclusion: This review found that obesity is a risk factor for dengue severity among children. The result highlights and improves our understanding that obesity might influence the severity of dengue infection.